1994
DOI: 10.1007/bf01426390
|View full text |Cite
|
Sign up to set email alerts
|

Superfluorescent transitions in an external magnetic field

Abstract: Abstract. Polarisation properties of the superfluorescence in the near-infrared regime have been investigated between high-lying levels of Sr and Ba under the influence of a static homogeneous external magnetic field. In some transitions the time-resolved measurements show a change of the polarisation of the superfluorescence depending on the magnetic field strenght. In suitable experimental conditions intensity modulations were observed. These were assigned as Zeeman quantum beats or indirectly observed Zeema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…2). Recently it was shown that the superfluorescence pulse starts with the polarization of the laser pulse in the second excitation step [6,7]. Since in our measurements the linear polarization of the superfluorescence pulse was parallel to the direction of the magnetic field, there was no dependence of the direction of the polarization of the superfluorescence on the magnetic field strength.…”
Section: Measurementsmentioning
confidence: 96%
See 4 more Smart Citations
“…2). Recently it was shown that the superfluorescence pulse starts with the polarization of the laser pulse in the second excitation step [6,7]. Since in our measurements the linear polarization of the superfluorescence pulse was parallel to the direction of the magnetic field, there was no dependence of the direction of the polarization of the superfluorescence on the magnetic field strength.…”
Section: Measurementsmentioning
confidence: 96%
“…The experimental set up is the same as already presented [6]. Let us briefly recall that the Ba atoms in an atomic beam were excited stepwise via the 6s6p P level into a 6snd D level by two polarized dye laser pulses.…”
Section: Measurementsmentioning
confidence: 99%
See 3 more Smart Citations